Innovation versus Replication: Some Notes on the Approaches in Defining Shariah Compliance in Islamic Finance - Mohamad Akram Laldin; Hafas Furqani (Al-Jami'ah Research Centre, 2016)
Shariah contains the principles and foundations upon which financial system from an Islamic perspective is established and acts as guidance and framework on which the direction of the industry is set. This would include the whole processes from product conceptual inception of developing shariah product compliance manual, developing product structure, reviewing the legal documentation, and producing report or opinion on the product application in the market. Islamic finance is expected to offer something new to the market instead of a mere replication and modification of conventional practices in Islamic forms. The paper attempts to survey the approach in developing Islamic finance, including the debate on replication and innovation in a product to the structure as well as the gaps between ideals and practices. [Keuangan Islam dikembangkan berdasarkan atas semangat, filosofi dan prinsip-prinsip hukum Islam sebagaimana terangkum dalam ekonomi shariah. Makalah ini berusaha mengamati berbagai pendekatan dalam mengembangkan keuangan Islam, perdebatan mengenai replikasi ekonomi konvensional, dan inovasi dalam produk hingga struktur maupun kesenjangan antara yang ideal dengan kenyataannya. ]